A framework and pilot tool for the risk-based prioritization and grouping of nano-enabled consumer products. Issue 1 (21st December 2018) - Rycroft, Taylor; Larkin, Sabrina; Ganin, Alexander; Thomas, Treye; Matheson, Joanna; Van Grack, Tessa; Chen, Xinrong; Plourde, Kenton; Kennedy, Alan; Linkov, Igor
Abstract : The growing number of nano-enabled consumer products can now be effectively prioritized according to their potential human health risk. Abstract : The use of engineered nanomaterials (ENMs) in consumer products has expanded rapidly, revealing both innovative improvements over conventional materials, and the potential for novel risks to human health and the environment. As the number of new nano-enabled products and the volume of toxicity data on ENMs continues to grow, regulatory agencies like the U.S. Consumer Product Safety Commission (CPSC) – a small, independent federal agency responsible for protecting consumers from unreasonable risks associated with product use – will require the ability to screen and group a diverse array of nano-enabled consumer products based on their potential risks to consumers. Such prioritization would allow efficient allocation of limited resources for subsequent testing and evaluation of high risk products and materials. To enable this grouping and prioritization for further testing, we developed a framework that establishes a prioritization score by evaluating a nano-enabled product's potential hazard and exposure, as well as additional consideration of regulatory importance. We integrate the framework into a pilot-version software tool and, using a hypothetical case study, we demonstrate that the tool can effectively rank nano-enabled consumer products and can be adjusted for use by agencies with different priorities. The proposed decision-analytical framework and pilot-version tool presented here could enable a regulatory agency like the CPSC to triage reported safety concerns more effectively and allocate limited resources more efficiently.